The evaluation of the burden of multisystem inflammatory syndrome in children on health economics - Ezgi Balkarlı; Elif Kıymet; Elif Böncüoğlu; Şahika Şahinkaya; Miray Yılmaz Çelebi; Hurşit Apa; Timur Meşe; Hasan Ağın; Süleyman Nuri Bayram; İlker Devrim (Archives of Rheumatology, 2024)
Objectives: This study aimed to evaluate the diagnostic tests and treatments applied in patients with multisystem inflammatory syndrome in children (MIS-C) and to determine the effect of the disease on health costs. Patients and methods: This retrospective cohort study included 59 MIS-C patients (40 males, 19 females; mean age: 7.7±4.2 years; range, 4 months to 16.5 years) who were admitted and treated between April 1, 2020, and November 1, 2021. Demographic and clinical features with hospital costs and length of stay were retrospectively reviewed from the medical files and computerized system of the hospital. Direct medical care costs of items were calculated with the hospital perspective using a combination of microcosting technique (resource-based accounting method) and hospital list data. Cases were classified as mild, moderate, or severe, and the patients were divided into two groups: the mild group and the moderate-severe group. Classification was determined by the vasoactive inotropic score (VIS), degree of respiratory support, and evidence of organ damage. Results: The mean age of the cases in the mild group was 6.5±3.7 years, and the mean age of the cases in the moderate-severe group was 9.2±4.3 years. Of 59 patients, 19 (32.2%) were followed up in the pediatric intensive care unit. The median duration of hospitalization in the hospital was 8 (interquartile range: 7-12) days. The total cost of the patients hospitalized with the diagnosis of MIS-C during the study period was 849,242.93, and the mean cost per patient was 14,393.94±9,631.92. In the distribution of the total cost of hospitalization according to expenses, the highest rate was pharmacy and blood products (51.99%) and IVIG costs (43.99%). While the mean total cost per person was 13,682.87±8,799.63 in mild cases, it was 16,433.82±9,440.02 in moderate-severe cases, and no statistically significant relationship was found between the two groups (p>0.05). There was no difference in the mean cost per patient between the cases with and without heart, lung, kidney, or neurologic involvement and advanced respiratory support (p>0.05). There was a strong positive correlation between the total costs and age (r=0.883, n=59, p<0.0001), with increased amount of costs with increased age. Conclusion: In the study, no statistically significant correlation was found between the total cost of per person in the mild group and the moderate-severe group (p>0.05). This finding may be due to the wide use of IVIG in MIS-C treatment, in addition to low transfer rates to pediatric intensive care units due to high-flow nasal cannula usage.